The Influence of Teamwork and Reward on Employee Performance at Hisana Fried Chicken Makassar City - Rohani Rohani; Zalkha Soraya; Rahayu Japar (Journal Social Society, 2026)
Urgency of the study: This study is essential to examine how teamwork and reward systems influence employee performance, thereby providing valuable insights for improving organizational effectiveness and service quality at Hisana Fried Chicken Makassar City. Employee performance is a critical factor in achieving organizational goals and maintaining business competitiveness. According to human resource management theory, effective teamwork and appropriate reward systems are among the key determinants of employee performance, as they enhance motivation, collaboration, and work effectiveness. This study aims to examine the influence of teamwork and reward on employee performance at Hisana Fried Chicken Makassar City. The research employed a quantitative approach using a survey method. Data were collected through Likert-scale questionnaires distributed to 210 employees selected using a saturated sampling technique, in which all members of the population were included as respondents. The collected data were analyzed using multiple linear regression. The results indicate that teamwork has a positive and significant effect on employee performance (p < 0.05). Likewise, reward demonstrates a positive and significant influence on employee performance (p < 0.05). Simultaneously, teamwork and reward account for 53.7% of the variance in employee performance (Adjusted R² = 0.537). Furthermore, reward was found to have a more dominant effect than teamwork in improving employee performance. These findings support motivational and organizational behavior theories, which emphasize the importance of recognition and collaborative work environments in enhancing employee outcomes. The practical implication of this study is that organizations should strengthen teamwork practices and optimize reward systems to improve employee performance. In conclusion, both teamwork and reward significantly contribute to employee performance, with reward emerging as the most influential factor.